Stress corrosion crack initiation in Alloy 690 in high temperature water. Issue 1 (February 2018) - Moss, Tyler; Kuang, Wenjun; Was, Gary S
Highlights: Alloy 690 is resistant to stress corrosion crack initiation. Only dynamic strain tests have generated primary water SCC initiation in Alloy 690. A mechanism of stress corrosion crack initiation is proposed consisting of: (i) oxidation, where a protective film of Cr2 O3 is formed over grain boundaries; (ii) incubation, where oxide film rupture and repair depletes the grain boundary of Cr; (iii) nucleation, where the depleted grain boundary forms grain boundary oxides. Abstract: Initiation of stress corrosion cracks in Alloy 690 in high temperature water is a rare occurrence and depends on the method by which the sample is loaded. Only in dynamic straining experiments is crack initiation consistently observed. Stress relaxation in constant deflection tests, and lack of a means of rupturing the oxide film in constant load tests are the principle reasons for the difficulty of initiating cracks in these tests. These observations, combined with those from the much more susceptible Alloy 600 form the basis for a mechanism stress corrosion crack (SCC) initiation of Alloy 690. SCC initiation is proposed to occur in three stages: an oxidation stage in which a protective film of Cr2 O3 is formed on the surface over grain boundaries, an incubation stage in which successive cycles of oxide film rupture and repair depletes the grain boundary of chromium, and a nucleation stage in which the chromium depleted grain boundary is no longer able to support growth of a protective chromium oxide layer, resulting in formation and rupture of oxides down the grain boundary. The mechanism is supported by the available literature on oxidation and crack initiation of Alloy 690 in hydrogenated primary water conditions.